An accurate cellular assay to determine pathogenicity of coding and noncoding variants in Lynch syndrome genes - Iris E. Glykofridis; Marleen Dekker; Chantal Stoepker; Thomas W. van Ravesteyn; Yvonne Tiersma; Cédric G. van der Ham; Beaunelle de Bruijn; Salma Ebrahim; Renée X. de Menezes; Esmee Kasteleijn; Frans Verheijen; Tjakko J. van Ham; et al. (Proceedings of the National Academy of Sciences, 2026)
Lynch syndrome (LS) is a genetic predisposition to mainly colorectal and endometrial cancer due to heterozygous disruptive germline mutations in the DNA mismatch-repair (MMR) genes MSH2 , MSH6 , MLH1, or PMS2 . Beyond clearly pathogenic mutations, germline sequencing often reveals variants of uncertain significance (VUS), predominantly single base-pair alterations in coding or noncoding regions. These uncertain variants obstruct LS diagnosis, hampering personalized surveillance. To address this challenge, we developed a highly accurate functional assay that interrogates VUS pathogenicity in human cells. Building on a mouse-based cellular assay, we adapted oligonucleotide-directed mutation screening (ODMS) for human cells and introduced a refined approach named “coselection ODMS.” To ensure physiological expression, the variant is introduced into the endogenous MMR gene by replication-coupled gene editing. Coselection ODMS demonstrated 100% accuracy in classifying 50 benign and 86 pathogenic variants spanning coding and noncoding regions in all four MMR genes. Among 109 patient-derived VUS, 51 were identified as deleterious for MMR function. Importantly, coselection ODMS delivered 100% concordant results in a clinical diagnostic laboratory. With >93% sensitivity and >92% specificity, coselection ODMS provides a highly reliable functional assay in the diagnosis of enigmatic LS variants, enabling risk assessment and personalized surveillance or treatment for affected families.